Enhancing Children's Storytelling Skills Through a Picture Story Approach - Yusuf Kamaruddin, Muhammad; HF, Alkifrah Daniyal.; Lesbatta, Delkia (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the implementation of storytelling methods supported by visual media to enhance storytelling skills in early childhood. The research was conducted at KB Aurora, Latta, Indonesia, using a classroom action research design consisting of two intervention cycles, involving 11 children aged 5ÔÇô6 years. In each session, theme-based storytelling was combined with the use of visual media to support the learning process. The results showed a significant improvement in the children's storytelling skills. Before the intervention, more than half of the participants were categorized as